Analytical Method for Heat Conduction Problem with Internal Heat Source in Irregular Domains. (13th November 2013) - Fan, Hongming; Tang, Sen; Hua, Jin; Yu, Hang
Abstract : In engineering field, analytical methods can only be applied to classic heat transfer problems with regular geometric boundaries. It is difficult to apply analytical methods in solving the mathematical and physical equations in nonorthogonal boundary of irregular domains. In this paper, we presented a method by conformal mapping from the solution for heat conduction problems in regular domains to solve problems in irregular domains.